IMPROVING STUDENTS™ SPEAKING ACHIEVEMENT IN ORAL DESCRIPTIVE TEXT BY USING VIDEO - Manalu, M. Eryca Ronauli; Arifin, Tina Mariany (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
AbstractThis research aims at improving students™ achievement in oral descriptive text usingvideo by conducting a classroom action research (CAR). The subjects were Grade X,students of State Senior High School (Sekolah Menengah Atas Negeri: SMAN) 17Medan, the total number of the students was 39 students. The research was carriedout in two cycles with three meetings in each cycle. There were two kinds of datacollected during the research, quantitative and qualitative data. The instruments forcollecting the quantitative data were spoken tests, while for qualitative data, gatheredthrough observation sheet, interview, questionnaire, and diary notes. Based on thedata analyses, the mean of the students™ score in the orientation test was 53.9, inCycle I was 65.09, and in Cycle II was 75.34. Based on the mean scores, it can beconcluded that the students™ speaking achievement in oral descriptive text by usingvideo showed a significant improvement from 53.9 to 75.34. Therefore, it issuggested that teachers should try to use varieties of presentations in uplifting thestudents™ achievement in speaking.Keywords: Speaking, Students™ Achievement, Oral Descriptive Text, Video